Infection processes of Ciborinia camelliae on camellia flower tissue - Vingnana-Singam, V.; Long, P.G.; Rowland, R.E. (New Zealand Plant Protection, 2000)
The infection process of Ciborinia camelliae the cause of camellia flower blight was studied using light and confocal microscopy Germination and infection structures of the pathogen on petals were stained with trypan blue in lactophenol and with glutaraldehyde for light and confocal microscopy respectively Within 6 h of inoculation the ascospores germinated and formed short germ tubes The host cuticle was penetrated and within a further 6 to 18 h a large swollen structure formed underneath each penetration From here a hypha grew under the cuticle to the junction between two cells and then developed as intercellular hyphae The mycelium continues to develop intercellularly for the next 72 h but without causing extensive destruction of the host cell walls